Influence of Ultrastructural Corneal Graft Abnormalities on the Outcome of Descemet Membrane Endothelial Keratoplasty - Weller, Julia M.; Schlötzer-Schrehardt, Ursula; Tourtas, Theofilos; Kruse, Friedrich (American Journal of Ophthalmology, 2016)
To investigate if ultrastructural alterations in the Descemet membrane (DM) are correlated with the clinical outcome after Descemet membrane endothelial keratoplasty (DMEK).Retrospective cohort study.setting: Institutional, single-center.One hundred and twelve residual DM specimens obtained after DM stripping.Incidence of ultrastructural abnormalities in transmission electron microscopy, graft detachment rate, graft failure rate, best-corrected visual acuity (BCVA), endothelial cell density (ECD), and central corneal thickness (CCT). Examination dates were on the day before DMEK and 1, 3, 6, and 12 months after surgery.Abnormalities in the ultrastructure of DM were found in 16 of 112 specimens (14%) (abnormal DM group), comprising deposits of long-spacing collagen, fine filaments (proteoglycans), a posterior collagenous layer, pseudoexfoliative material, and guttae. The secondary graft failure rate was significantly higher in the abnormal DM group compared with the normal DM group (P = .001). There was a trend for an increased graft detachment rate in the abnormal DM group (11/16) compared with the normal DM group (42/96) (P = .103). There was no significant difference in mean CCT and ECD after surgery. Mean CCT in the eyes with graft failure in the abnormal DM group at the last follow-up before regrafting was 850 ?m, indicating endothelial failure with stromal edema.This study reveals a correlation between ultrastructural alterations of DM in donor corneas and the graft failure rate after DMEK. Thus, graft failure after DMEK not only is determined by surgical trauma and postoperative events but may also be influenced by intrinsic, graft-specific features.
EVALuna2:21302